An unfortunate injection. (1st March 2016) - Shah, Bhavik Sandip; Yarbrough, Chase; Price, Amy; Biswas, Rakesh
Abstract : Intramuscular injection has been used to administer medications for more than a hundred years. However, despite our profession's long experience with intramuscular administration, preventable complications such as injection nerve palsies are still prevalent in developing countries. Injections account for one-fifth of all traumatic nerve injuries. These injuries largely occur due to indiscriminate use of intramuscular injections for treating common illnesses, frequently by unlicensed or undertrained practitioners administering unnecessary treatment to impoverished patients. The sciatic nerve is the most commonly injured, and frequently the resulting muscle weakness and associated disability are irreversible. This case report includes a video of a patient with foot drop 6 weeks after gluteal intramuscular injection. Such injuries can be prevented by proper awareness and training, the implementation of safer injection techniques, and quality assurance methods.